Choice of foreign market entry mode - Exploring foreign automobile manufacturing firms’ entry strategies into China: a case study of BMW and Jaguar Land Rover (JLR). - Cai, Yining (2014)
China has become the world’s largest auto market through substantial FDI from foreign automakers in the last 30 years. Due to the complex institutional and business environment in China, foreign automakers should take various factors into consideration when selecting an entry mode into China. This paper aims to investigate how foreign automakers enter China and what factors influence their entry mode selection. To have an in-depth analysis of their entry strategies into China, this paper uses a qualitative case study method to analyze BMW’s and JLR’s entries into China. It is found that their entry and operation mode choices are influenced by a mixture of country-specific, firm-specific, industry-specific and project-specific factors. Among these various factors, Chinese government policy has remarkable impact on foreign automakers’ entry mode decisions. Due to government regulation of China’s automobile industry, joint venture (JV) is the most popular entry or operation mode used by foreign automakers. It is found that foreign automakers may face conflicts with Chinese partners concerning control and goal setting. To resolve the conflicts promptly and effectively, both of them should make concessions over benefits and rights.